2002
DOI: 10.2114/jpa.21.105
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Fat Distributions and Several Plasma Adipocytokines after Exercise Training in Premenopausal and Postmenopausal Women.

Abstract: Circulating concentrations of adipocytokines, such as leptin, tumor necrosis factor-α (TNF-α), and plasminogen activator inhibitor-1 (PAI-1), vary with exercise training, menopause, or regional variations in adipose tissues. In the present study, the relationships between body fat distributions and some adipocytokines w e r e c o m p a re d i n p r e m e n o pa u s al ( N = 9 ) a n d postmenopausal women (N=9), before and after exercise training. The training for 10 weeks (that is, 3 days/week) consisted of aq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
35
1
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 53 publications
8
35
1
6
Order By: Relevance
“…Two studies observing a positive relationship between leptin and breast cancer did not identify the menopausal status and included both pre-and postmenopausal patients in their analyses [36,38]. Menopausal status could be a confounding factor, as Cento et al [39] and Hayase et al [40] noted higher leptin levels in Fig. 1 Serum levels of A-FABP and leptin of all breast cancer patients related to tumor characteristics premenopausal than postmenopausal women.…”
Section: Adipocytokines Bmi and The Risk Of Breast Cancermentioning
confidence: 99%
“…Two studies observing a positive relationship between leptin and breast cancer did not identify the menopausal status and included both pre-and postmenopausal patients in their analyses [36,38]. Menopausal status could be a confounding factor, as Cento et al [39] and Hayase et al [40] noted higher leptin levels in Fig. 1 Serum levels of A-FABP and leptin of all breast cancer patients related to tumor characteristics premenopausal than postmenopausal women.…”
Section: Adipocytokines Bmi and The Risk Of Breast Cancermentioning
confidence: 99%
“…Weight reduction in obese subjects following a hypocaloric diet for 12 months resulted in signifi cant decreases of p-TNF- and p-IL-6 12 , whereas in contrast p-TNF- concentrations were not infl uenced by exercise training or induced weight losses in non-obese 13,14 and obese pre- 15 and postmenopausal 16 women. In the present study exercise training did not change body weight, p-leptin or p-insulin, whereas mean elevated p-glucose was signifi cantly lower after the intervention period.…”
Section: Discussionmentioning
confidence: 95%
“…In our study here, we selected the method of weight-loss for obese individuals to consist of a wellnutrient balanced dietary restriction and moderate intensity exercise habituation. The method of training is also one of the determinants of TNF-α levels, because contradictory levels of circulating TNF-α were observed after exercise training [5,[7][8][9]. Therefore, we suggest that differences in the use of the term "intervention", and/or the methods of exercise training used may account for the contradictory results in systemic inflammatory condition reported by different studies.…”
Section: -24]mentioning
confidence: 90%
“…On the other hand, our study did not show any change in the levels of TNF-α, a well-known inflammatory factor. Actually, some previous studies demonstrated that the effect of weightloss on circulating TNF-α levels have induced definitely different result, increase, decrease, or unchanged [5,[7][8][9]. Bruun et al showed that adipose TNF-α levels decreased after a 15-week period of dietary restriction and habitual exercise intervention, but the circulating TNF-α levels did not decrease [5].…”
Section: -24]mentioning
confidence: 99%
See 1 more Smart Citation